2009
DOI: 10.1016/j.ijgo.2009.08.033
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Metformin versus laparoscopic ovarian drilling in clomiphene‐ and insulin‐resistant women with polycystic ovary syndrome

Abstract: Although metformin results in a better attenuation of insulin resistance, laparoscopic ovarian drilling is associated with higher rates of ovulation and pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
43
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 26 publications
8
43
0
Order By: Relevance
“…Androgen excess in PCOS is believed to be the result of insulin's ability to increase androgen production by ovarian theca cells (22,23). The significant decline in postdrilling serum androgens and LH that is seen more obviously in patients who received an adjusted thermal dose could be explained by adequate thermal destruction of androgen-secreting stroma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Androgen excess in PCOS is believed to be the result of insulin's ability to increase androgen production by ovarian theca cells (22,23). The significant decline in postdrilling serum androgens and LH that is seen more obviously in patients who received an adjusted thermal dose could be explained by adequate thermal destruction of androgen-secreting stroma cells.…”
Section: Discussionmentioning
confidence: 99%
“…The major pharmacological action of metformin is reduction of glucose production by the liver and improvement of IR. It is widely used for treatment of PCOS‐related infertility symptoms, especially in those with CC resistance . Our metformin data agrees with previous studies, which showed significant decrease in WC, IR and T levels .…”
Section: Discussionsupporting
confidence: 92%
“…All women met the criteria for diagnosis of PCOS according to Rotterdam Consensus Group . CC resistance is defined as failure to ovulate with CC for at least 3 months at a dose of 150 mg/day for 5 days . The exclusion criteria included women under 20 or over 38 years and patients who had received gonadotrophins or hormonal contraception in the 3 months prior to the study.…”
Section: Methodsmentioning
confidence: 99%
“…It had no significantly higher chance at pregnancy or higher pregnancy rates in women with PCOS [6]. In patients with clomiphene resistance where it is being advocated, LOD was found to reduce testosterone and Luteinising hormone levels and associated with more regular cycles, higher ovulation and pregnancy rates compared to metformin alone even though metformin results in more attenuation of luteinizing hormone [28]. Emerging evidence shows that unilateral ovarian drilling has similar effects as bilateral ovarian drilling in bringing about ovulation, pregnancy rates, and life birth rates.…”
Section: Surgery and Ovulation Induction 41 Use Of Ovarian Drillingmentioning
confidence: 98%